Coma Blisters - Joana Rocha; Teresa Pereira; Filipa Ventura; Fernando Pardal; Celeste Brito (Karger Publishers, 2009)
Coma blisters are lesions that occur in the setting of a variety of neurological diseases. Although most commonly associated with barbiturate overdose, they can be seen in the setting of coma due to other etiologies. Blisters develop 48-72 h after the onset of unconsciousness. We report the case of a 29-year-old man who presented to the emergency department with confusion and progressive loss of consciousness. He had high serum glucose, abnormal hepatic and kidney function tests and a normal toxicological screening. 24 h after admission he was comatose and was started on antibiotics for presumed bacterial meningoencephalitis. Two days after the onset of coma, multiple tense hemorrhagic blisters appeared on the patient's extremities. Skin biopsy revealed an intraepidermal blister with variable degrees of epidermal necrosis. Five days later the patient was fully recovered with no neurological sequelae. No topical treatment was necessary, with complete resolution of the skin lesions two weeks later.